(untitled) (European Journal of Pure and Applied Mathematics, 2023)
This paper studies the epidemic model of rational order via an efficient genius modern analytical approximate technique named Natural Transform Adomian Decomposition Method (NTADM). It is based on Caputo fractional derivative. To demonstrate the effectiveness of the present method, the results are displayed in graphs. Accordingly, the NTADM can be very easily applied to other nonlinear models.